2020
DOI: 10.3390/ani10040682
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Thermal and High-Pressure Treatments on the Microbiological Quality and In Vitro Digestibility of Black Soldier Fly (Hermetia illucens) Larvae

Abstract: Black soldier fly larvae (BSFL) are gaining importance in animal feeding due to their ability to upcycle low-value agroindustry by-products into high-protein biomass. The present study evaluated the nutritional composition of BSFL reared on brewer’s by-product (BBP) and the impact of thermal (90 °C for 10/15 min) and high-pressure processing (HPP; 400/600MPa for 1.5/10 min) treatments on the microbial levels and in vitro digestibility in both ruminant and monogastric models. BBP-reared BSFL contained a high le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 33 publications
3
23
2
Order By: Relevance
“…These values are similar to previous studies which found BSFL to contain quantities of 2.3 log cfu/g of B. cereus [7]. Aerobic endospore formers present a challenge for edible insects [12,[47][48][49] due to the difficulty in irradicating them, therefore it is suggested that strategies be adopted to use feed with low aerobic spore counts to limit possible contamination [50]. The results from this study did not demonstrate B. cereus accumulation in the BSFL, as the BSFL had lower B. cereus than the feeds they were grown on.…”
Section: Discussionsupporting
confidence: 90%
“…These values are similar to previous studies which found BSFL to contain quantities of 2.3 log cfu/g of B. cereus [7]. Aerobic endospore formers present a challenge for edible insects [12,[47][48][49] due to the difficulty in irradicating them, therefore it is suggested that strategies be adopted to use feed with low aerobic spore counts to limit possible contamination [50]. The results from this study did not demonstrate B. cereus accumulation in the BSFL, as the BSFL had lower B. cereus than the feeds they were grown on.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, other fatty acids, such as lauric or myristic fatty acids, were present in BSFL but not in the rearing substrates. Lauric acid was the fatty acid present with the highest concentration, in agreement with other studies ( Spranghers et al 2017 , Campbell et al 2020 ), and it was synthesized from other nutrients present in the substrate, such as carbohydrates (starch and sugars) ( Spranghers et al 2017 , Ewald et al 2020 ). Moreover, recent evidence ( Hoc et al 2020 ) suggested the importance of carbohydrates as a source of acetyl-CoA in the BSFL fatty acid profile constitutions; the authors underlined the need to conduct further studies on the role of carbohydrate level in BSF diets as they are an essential source of acetyl-CoA, a critical molecule in the biosynthesis of fatty acids.…”
Section: Discussionsupporting
confidence: 90%
“…Considering the nutritive value for ruminants, unlike monogastrics, the in vitro rumen dOM was not affected by the rearing substrate, and the obtained values were lower than the in vitro DM true digestibility for ruminants obtained by Campbell et al (2020) , but higher than the values for OM reported by Jayanegara et al (2017) .…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…However, the nutritive value of these insects can be negatively affected if extensive heat treatments are applied. Previous data indicate that different heat treatments and high pressure can significantly reduce the microbial counts in fly larvae without affecting nutritive value and digestibility of the larva (Campbell et al, 2020). However, heat treatments that aim to reduce microbial counts without structurally damaging insects are highly useful when insects are used as feed for animals in order to prevent diseases caused by the presence of pathogenic bacteria in larvae (Caparros Megido et al, 2018;Rumpold et al, 2014).…”
Section: Introductionmentioning
confidence: 99%